Sustainable Finance for Promoting Inclusive Growth - I Gusti Ayu Purnamawati (Jurnal Ilmiah Akuntansi, 2021)
Various essential things will be revealed in this research on how sustainable financial performance promotes inclusive growth when the Indonesian state is experiencing a sizeable economic impact due to the covid-19 pandemic. Independent variables used to measure inclusive growth include divisia of money, fiscal policy, and green banking, while the dependent variable is inclusive growth. Multiple regression analysis was used for statistical data on developments for the last ten years per semester. The data collection by downloading statistical information and annual financial report data and analyzed using SPSS Version 20. This study indicates that divisia of money, fiscal policy, and green banking positively affect inclusive growth. The collaboration of various elements will benefit inclusive and equitable economic growth, providing opportunities for all levels of society to take part in decision-making and the use of resources. Green banking is expected to improve its reputation in the eyes of customers for its sustainability.